Exploring the Impact of Gadolinium on Microstructure, Thermodynamics, Mechanical Behavior, and Specific Heat Capacity in CuAlTa Shape Memory Alloy - Ercan, Ercan; Qader, Ibrahim Nazem; Dagdelen, Fethi; Kök, Mediha (My University, 2025)
The surface morphology, microstructure, phase transition and specific heat capacity C_P (T) of the alloys produced by enriching CuAlTa shape memory alloys with Gadolinium (Gd) were examined depending on temperature changes. This study shows that alloy composition and phase behavior are closely related to high martensitic phase transformation temperature (PTT). The addition of Gd to the alloys reduces the crystal size and significantly reduces the 18R phase. This relationship enables the design of new materials with customized properties. EDS analysis confirms the precipitation of tantalum in the ? phase, as a result of its limited solubility in the matrix, effectively preventing the martensitic phase transformation. Therefore, the PTT increased by increasing Gd additive in the alloy. On the other hand, increasing Gd in the alloy causes the surface under martensitic transformation to decrease, and as a result, it reduces the stability of the shape recovery effect, causing the C_P (T) to increase.
Keywords: Shape memory alloy; Cu-Al-Ta-Gd; high temperature phase transformation; specific heat capacity